Biodiesel Production by Direct Transesterification Process via Sequential Use of Acid–Base Catalysis - Yunus Khan, T.M.; Badruddin, Irfan Anjum; Ankalgi, R.F.; Badarudin, Ahmad; Hungund, B.S.; Ankalgi, Fazal R. (Springer Verlag (Germany), 2018)
It is a well-known fact that energy consumption is rapidly increasing due to population growth, higher standard of living and increased production. A significant amount of energy resources are being consumed by the transportation sector leading to fast depletion of fossil fuels and environmental pollution. Biodiesel is one of the technically and economically feasible options to tackle the aforesaid problems. Biodiesel seems to be a replacement to the diesel and can be commonly produced by two-step esterification–transesterification process. In the current research, single-step process of direct transesterification method is developed and is compared with conventional two-step esterification–transesterification method. The fuel properties of biodiesel produced by these two methods have been studied. The results revealed that fuel properties of biodiesel like calorific value, kinematic viscosity, flash point, density, acid value remained similar in both methods. However, the new method developed is superior with respect to reduced reaction time, lower acid value and increased biodiesel yield. The acid value of biodiesel obtained by single-step and two-step method was found to be 0.1 and 0.25 mg KOH/g, respectively. The new method was able to reduce the reaction time from 5 to 2 h. Yield of biodiesel was increased from 2 to 5% indicating advantages of new method compared to two-step conventional method.